Rapid in-situ synthesis, microstructure and mechanical properties of titanium matrix composites with micro/nano-sized TiB/TiC hybrid structures. (January 2023) - Zhang, Xinjiang; Yu, Wanjun; Wang, Juan; Wang, Pu; Liu, Zhaohui; He, Meng; Yang, Zirun
Abstract: Titanium matrix composites incorporating micro/nano-sized TiB/TiC hybrid structures were prepared utilizing the in-situ reaction of graphene/boron/titanium mixture powders by spark plasma sintering at 1100 °C for 5 min. Microstructural observation showed that the TiC micro/nano-scale particles homogeneously dispersed in the Ti matrix. Further observation revealed the TiC was polycrystal nanoparticles in the as-sintered bulk compacts. The uniform in-situ TiB whiskers formed by the boron/titanium reaction also exhibited the micro/nano-scale structure. The high hardness and compressive strengths, which increased by the more TiB fraction, were investigated through mechanical properties testing. The yield and ultimate compressive strengths of the composite (9.0 vol% reinforcements, TiB:TiC = 2:1) reached 1.86 and 2.18 GPa, respectively. This work represents an avenue to design and develop the homogeneous micro/nano-sized TiB/TiC hybrid structures, which were beneficial to mechanical response. The relevant strengthening mechanisms were discussed. Highlights: In-situ TiB/TiC hybrid reinforced TMCs were rapidly synthesized. The uniform TiC particles and TiB whiskers formed the micro/nano-sized structure. The polycrystal TiC nanoparticles were formed by graphene/titanium reaction. The composites exhibited the outstanding hardness and compressive strengths.